Goiter - Causes and Treatment 2020
DOI: 10.5772/intechopen.91627
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Nodule: Approach and Management

Abstract: A thyroid nodule is a discrete radiologically distinct lesion in the gland parenchyma. These are a common finding in the general population, majority being diagnosed incidentally during neck imaging. The major clinical relevance lies in the fact that 4-6.5% of nodules can be malignant. A thorough clinical evaluation and examination should be followed by serum TSH assessment and ultrasonography for assessment of size, number, imaging characteristics suggestive of malignancy, cervical lymphadenopathy. FNA should… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0
17

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(33 citation statements)
references
References 40 publications
0
16
0
17
Order By: Relevance
“…Different clinical features have been described as predictors of malignancy in thyroid nodules. These include the history of hoarseness of voice, history of the rapid growth of the nodule, fixation to surrounding structures, hard consistency of the nodule, and the illdefined surface of the nodule [21,22] . Furthermore, old age, male sex, solitary nodule, and larger size of the nodule are thought to be associated with increased risk of malignancy [9,23] .…”
Section: Discussionmentioning
confidence: 99%
“…Different clinical features have been described as predictors of malignancy in thyroid nodules. These include the history of hoarseness of voice, history of the rapid growth of the nodule, fixation to surrounding structures, hard consistency of the nodule, and the illdefined surface of the nodule [21,22] . Furthermore, old age, male sex, solitary nodule, and larger size of the nodule are thought to be associated with increased risk of malignancy [9,23] .…”
Section: Discussionmentioning
confidence: 99%
“…This analysis has a sensitivity of 92%, specificity of 48-53%, negative predictive value (NPV) of 93%, but low PPV thus being used as a rule out test to identify benign nodules. 1 Molecular testing is only applicable when combined with clinical and US malignancy features. Study by Kim et al [15] showed that suspicious of malignant cell (SMC) from repeat FNA or BRAFV600E mutation in cytopathologic specimen should be a trustworthy surrogate for malignancy and can be considered to proceed with surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasonography (US) reported can detect the nodule as high as 67%. [1][2][3] Fine needle aspiration (FNA) is the most valuable, cost effective and accurate method in the evaluation of thyroid nodule. The sensitivity was reported 65-98% and specificity 72-100%.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Los nódulos tiroideos son lesiones glandulares con características radiológicamente distintas al tejido circundante. Son hallazgos que se pueden presentar en más de la mitad de los pacientes sanos, sin embargo, generan preocupación tanto en el paciente como en el médico (1,2). Si bien la mayoría de los casos resultan ser nódulos benignos, su desafío clínico radica precisamente en identificar los que no lo son, mediante una historia clínica y un examen físico orientado a encontrar factores de riesgo personales y familiares, indagar la presencia de síntomas compresivos y explorar ganglios linfáticos cervicales (3,4).…”
Section: Introductionunclassified